Manajemen Pembatasan Penggunaan Kemasan Plastik Sekali Pakai Di Kota Palu - Nurfadilla, Ellis; Munari; Firmansyah, Andi Maman (JPS: Journal of Publicness Studies, 2026)
This study aims to determine the Management of Restrictions on the Use of Single-Use Plastic Waste in Palu City. This study uses a qualitative descriptive method. The theory used in this study is Henry Fayol's theory 1954. Based on the results of the study, it shows that the Management of Restrictions on the Use of Single-Use Plastic Packaging in Palu City cannot be said to be running well. although in the planning aspect the Palu city government and the Environmental Service have prepared strategic plans and plastic waste reduction programs. The Organizing aspect has not been optimal due to limited resources and inadequate facilities and infrastructure. Commanding is also not optimal because the provision of incentive support for those on duty in the field is lacking, which has an impact on the performance of officers in addition to the dissemination of information only focused on social media. The Coordinating aspect has been carried out through monthly internal meetings and communication media, but it also needs to be improved socialization to the community. The Controlling aspect has been monitored directly in the field, but it is not evenly distributed So there are some business actors who still use plastic bags.